إشكالات تنفيذ أحكام و قرارات القضاء الإداري - رضواني، نسرين (جامعة الوادي University of El Oued, 2024)
يعتبر موضوع إشكالات تنفيذ الأحكام القضائية الإدارية في مواجهة الإدارة من المواضع المهمة لما تطرحه من قضايا متشابكة على المستوى القانوني و القضائي ، و ذلك لإنتهاك الإدارة حقوق و حريات الأفراد كونها تتمتع بامتيازات السلطة العامة ، و التي من خلالها تتذرع عن القيام بتنفيذ الأحكام القضائية لاسيما الإدارية منها ، إن تنفيذ الإدارة لأحكام القضاء الصادرة ضدها اختياريا و ضمن الآجال القانونية ، إذا ما دل على شيء فهو يدل على احترام الإدارة للأحكام القضائية ، و كذا احتراما لحجية الشيء المقضي به ، من ثم خضوعها لمبدأ إلزامية التنفيذ . أما التنفيذ الجبري يجد مجاله ضد الإدارة في حالة امتناعها عن التنفيذ ، و لما كان الأمر كذلك من الضروري البحث و التقصي عن وسائل بديلة لضمان حرمة و هيبة القرارات القضائية الإدارية و يمكن أن تتمثل هذه الوسائل في الأوامر القضائية و الغرامة التهديدية . The issue of the problems of implementing administrative judicial rulings vis-à-vis the administration is considered one of the important issues because of the intertwined issues it raises at the legal and judicial level, due to the administration’s violation of the rights and freedoms of individuals as it enjoys the privileges of public authority, through which it excuses itself from implementing judicial rulings, especially administrative ones. Among them, the administration’s implementation of the judicial rulings issued against it voluntarily and within the legal deadlines, if it indicates anything, indicates the administration’s respect for the judicial rulings, as well as respect for the validity of the matter decided, and therefore its submission to the principle of mandatory implementation. As for forced implementation, it finds its scope against the administration in the event that it refrains from implementing it. Since this is the case, it is necessary to search and investigate alternative means to guarantee the sanctity and prestige of administrative judicial decisions. These means may be represented by judicial orders and threatening fines.
ماستر اداري